MORPHOLOGICAL CHARACTERIZATION AND GENETIC VARIABILITY IN FRENCH BEAN (Phaseolus vulgaris L.) GENOTYPES UNDER SUBTROPICAL CONDITION OF SRINAGAR GARHWAL - BISHT, RISHIBALA; D.K. RANA; K.N. SHAH; SINGH , VIVEK; RANA, HIMANI (The Bioscan, 2023)
In this study, 26 traditional French bean (Phaseolus vulgaris L.) genotypes collected from diverse regions in Uttarakhand, Himachal Pradesh, Jammu and Kashmir, and Manipur were evaluated for their genetic variability and morphological traits using RCBD with three replications. The morphological characterisation analysis revealed a reasonable amount of variation. Among the different traits under study, only pod stringiness showed 100% frequency. The analysis of variance indicated the mean sum of squares due to genotypes was highly significant at the 1% level of significance for all the characters. High GCV and PCV were found for characters like plant height (45.46, 45.5), fresh weight of nodules (28.68, 29.9), dry weight of nodules (51.59, 55.4), and number of pods per plant (27.32, 27.9), pod yield per plant (35.51, 37.5), and green pod yield per hectare (36.30, 42.2). High heritability estimates coupled with high genetic gain were observed for yield and other horticultural traits. A higher production was recorded by 25 genotypes that performed better than the check cultivar in terms of yield and other yield-related parameters. These genotypes can be taken into account for future plans for French bean breeding and suggested for cultivation in the subtropical climate of the Garhwal Hills.